Venom immunotherapy and pregnancy - Pałgan, Krzysztof; Żbikowska-Götz, Magdalena; Chrzaniecka, Elżbieta; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : The efficiency of venom immunotherapy (VIT) has been well documented by many studies. However, the most important for VIT is safety, particularly for a pregnant woman and a fetus. Aim : To establish the influence of continuation of VIT on pregnant women and offspring. Material and methods : The 6 women became pregnant during a specific immunotherapy. We retrospectively analyzed the influence of the immunotherapy on any complications for the pregnant women and their infants. Results : Of the 6 patients who participated in this study, four had hyperemesis gravidarum, nausea, and heartburn, and two of them had gestational diabetes mellitus symptoms, typical of pregnancy. The observation indicated that VIT was safe for the pregnant women and their offspring. Conclusions : The VIT is an appropriate therapeutic method for most patients with severe anaphylactic reactions after a hymenoptera sting. The observation indicated that VIT is safe for pregnant women and for their infants.